IMPROVING COMMUNICATION DEVELOPMENT AND LANGUAGE EDUCATION TOOLS IN THE CASE OF YOUNG LEARNERS - MARIA CLAUDIA CUC (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. Language and communication are psychological mechanisms at hand and subject of personal conduct adjustment and of the conduct of others. If the system images, concepts and ideas, formed through operational mechanisms of information were not to be used, then they would have no practical use, they would not be able to influence and inter-influence, but at the same time they should not be retrieved and returned to the circuit knowledge and should not have any impact on human activity. Communication, understood as an act of transactional action inevitably becomes essential to life, to the personal and social life of the individual. Pedagogical approaches used to encourage communication and development, while enriching and educating students in primary school includes space, adequate time and a set of tools meant to drive innovation and uniqueness through their involvement in the educational activity, in the well grounded educational institution. This requires the targeting of teaching based on psychological knowledge of the capabilities, skills and educational interests of students for effective action.